The Role of Stakeholders in the Successful Implementation of the Corporate Social Responsibility Program : (Studi Kasus Program CSR TPST Masa Sejati PT Kilang Pertamina Internasional RU V Balikpapan) - Robi'a Al Adawiyah; Nugrahaini, Lifania Riski (Indonesian Journal of Social Responsibility Review (IJSRR), 2022)
The success of the program in implementing Corporate Social Responsibility (CSR) can be demonstrated through the involvement of stakeholders both from local communities in the development area and from outside. Domination is often an obstacle in the sustainability of the program. The TPST Masa Sejati CSR sustainability program can’t be separated from how the actors in it play a role. This study wants to see how the role of stakeholders in the success of the CSR program in TPST Masa Sejati, Margasari Village. This study uses a qualitative descriptive method to explain how the actors are running in the empowerment program. The results of this study indicate that the direction of the TPST Masa Sejati program is very dependent on the role of local actors. The domination of actors in every activity with full authority makes members don’t have the opportunity to express their innovations. Members have every activity run to local actors as program Chair. This has an impact on the regeneration of actors for future program development.